World Trade Architecture. The Twin Towers and global financial centers - Leconte, Uta (International Planning History Society Proceedings, 2018)
Currently, over 300 World Trade Center’s exist worldwide in more than 80 countries, functioning as nodes within a global infrastructure, dedicated to promoting global business development. However, almost fifty years since the inception of the World Trade Center Association, the denomination ‘World Trade Center’ remains almost exclusively designated to the World Trade Center Complex in New York, with its iconic Twin Towers functioning as representation of capital, power and global trade far beyond their destruction in 2001.The starting point of the proposed paper is the timely coincidence of the completion of the World Trade Center Complex in New York in the early1970s and the implementation of a new interdependent global currency system, marked by the end of the Gold Standard in 1973 and the initiation of fiat money. Arguing that the specific identity and symbolism of the Twin Towers and the New York World Trade Center has since helped to stabilize an unstable global financial system, this paper asks: what are the effects of the New York Twin Towers on the planning of Financial Centers worldwide? It seeks to examine, how the specific identity of the New York World Trade Center was created, what it served, how it has been maintained over time, and what its effects are on urban planning on a local and global scale. The paper will first describe the relation between finance, architecture and the built environment as well as its sociocultural impact, taking as an example the New York Twin Towers and the concurrent implementation of a new global financial system in the early nineteen seventies. It will then focus on local effects of the Twin Towers and the World Trade Center by looking at its planning history and the urban transformation of Lower Manhattan from port and radio district to World Financial Center, including both stakeholders involved in the project as well as the cultural, political and economic urban context of Manhattan at the time. Finally, it will explore the global effects of the Twin Towers on the planning of financial centres and its urban impacts. By looking at the planning history, effect and impact of the Twin Towers on global financial centers, this paper aims to shed light on the specific agency of architecture as a symbolic object for urban planning, world trade and global connectivity.